Relationship between brain-derived neurotrophic factor serum levels with the severity of melasma - Putri Astrid Novianti Nazli; Ariyati Yosi; Khairina Nasution (Medicinski glasnik, 2023)
Aim: To determine the relationship between brain-derived neurotrophic factor (BDNF) levels and the severity of melasma. Methods: This cross-sectional analytic study included consecutive patients from the Dermatology and Venereology Polyclinic at Prof. dr. Chairuddin Panusunan Lubis Universitas Sumatera Utara (Prof. dr. CPL USU) Hospital Medan from May to December 2022. Serum BDNF levels and the severity of melasma were analysed using the Kruskal-Wallis test. Results: Of the total of 30 patients enrolled in the study, the majority were in the age group of 36-45 (average of 44) years and work as housewives. The highest risk factor was sun exposure. The melasma pattern was dominated by centrofacial patterns, majority of melasma types were epidermal, and the most severe degree was moderate. A moderate negative correlation between BDNF levels and the duration of melasma was found (p=0.007; r= -0.485). There was no significant relationship between BDNF levels and the severity of melasma (p=0.387). Conclusion: No significant relationship between BDNF levels and the severity of melasma indicates that the causes of melasma are multifactorial, such as sun exposure, genetic, hormonal, and other factors (drugs, neural and psychological, and lipid metabolism).
Keywords: melanosis; brain-derived neurotrophic factor; nerve growth factor